Clínica de Direitos Humanos: uma alternativa de formação em Direitos Humanos para cursos jurídicos no Brasil - Lapa, Fernanda Brandão (2014)
The purpose of this study was to identify an additional space in the Brazilian legal courses for the training of law student, graduate or post-graduate, that would be able to promote the integration between teaching, research and outreach, and also to articulate the theory and practice of Human Rights in an interdisciplinary way. Whereas education in Human Rights is present in Brazilian universities and, as well, as in other countries, a research in the academic literature was made in order to verify spaces in which Human Rights education occurs and how it occurs. The diagnosis of this research is that university lacks a space or forum where teaching, research and outreach are integrated. Semi-structured interviews were conducted with coordinators of Human Rights spaces in five Brazilian universities to identify the similarities and differences between their views and activities. This study reachs the conclusion that a Human Rights Clinic that fulfills, at least, seven requirements (1. commitment to Social Justice; 2. participatory methodology ; 3. articulation of theory and practice on Human Rights; 4. integration of teaching, research and outreach activities; 5. interdisciplinary approach ; 6. institutionalization and recognition in the university ; 7. targeted in university public) can be a space that ensures effective Human Rights education for Law Schools in Brazil